Pendidikan pembangunan modal insan - Azhar Hj. Wahid; Zawawi Yahya (Tanjong malim, Perak : Penerbit Universiti Pendidikan Sultan Idris, 2009)
Issues on the role of education in developing human resources in Malaysia.
Keywords: Education -- Malaysia; Human capital -- Malaysia